O ensino de história no primeiro Gymnasio da Capital (1894 1931) - Faria, Joana Borges de (2012)
Identify the History discipline educational finality in the first Ginásio de São Paulo, its contents and pedagogical methods between 1894, date of its implantation, and 1931, year when occurred the Francisco Campos Reform, in witch was proclaimed the serial system‟s normalization and the preparatory course‟s extinction, in order to comprehend the processes of History discipline‟s consolidation within incipient public secondary school curriculum in São Paulo. Therefore, it was analyzed, in the study period, the Ginásio da Capital History‟s teaching plan; federal and São Paulo state‟s laws; São Paulo house of representatives‟ annals, state secretaries‟ reports, in order to recover the governmental prescriptions and political impingement over History teaching in secondary course. Furthermore, the historical documents in the school‟s archive, were consulted, as an effort to identify the History‟s educational practices: minutes and exams of History teacher‟s contest, final and promotional exams, congregation‟s minutes, school‟s bulletins, mail and school‟s annual reports. The reserch proceeds along André Chervel‟s investigation, that studies school through school discipline‟s history and understand this institution as an own knowledge producer. The school disciplines aren‟t, therefore, a transposition of the reference science, but it is constituted inside the school, dedicated to instruct children and adolescents, from educational finalities imposed by society. In order to comprehend the history of the History‟s discipline on secondary school, in São Paulo, at that period, it‟s necessary to find out how the contents were used according to a specific finality